Combined analyses of costs, market value and eco-costs in circular business models: Eco-efficient value creation in remanufacturing - Joost G. Vogtlander; Arno E. Scheepens; Nancy M. P. Bocken; David Peck (Journal of Remanufacturing, 2017)
Eco-efficient Value Creation is a method to analyse innovative product and service design together with circular business strategies. The method is based on combined analyses of the costs, market value (perceived customer value) and eco-costs. This provides a prevention-based single indicator for 'external environmental costs' in LCA. The remanufacturing of products is an environmental and sustainable approach, in the circular economy, and can deliver lower eco-costs of materials depletion and pollution. From a business point of view, however, remanufacturing seems to be viable in B2B niche markets only. In consumer markets, remanufacturing is less common. The question is how can remanufacturing become a viable business solution for mainstream consumer markets. Traditional 'green' marketing approaches are not enough: green has a positive, but also negative connotations, so marketing approaches are complex. By using the Eco-efficient Value Creation method, marketing strategies for the roll-out of remanufacturing in mainstream consumer markets, can be revealed. This approach has led to the development of five aspects, which are key to innovative circular business models, for remanufacturing: (1) buyers differ from the buyers of the 'new product' (2) quality must be emphasised in all communications (3) risk must be taken away from the buyer (4) top level service is required to convince the buyer (5) a 'green' brand may support the remanufactured product image.
Keywords: 650; Eco-cost; Life cycle analysis; Reuse; Remanufacturing; Sustainability; Closed loop